Pengaruh Ambient Condition Terhadap Repurchase Intention Di Dua Pintu Coffe Padang - Hafifa Nurul Fuada; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by several problems, namely the number of repeat orders from visitors is still low, there are visitors who complain about the place being noisy because the music is loud and close to the road, the parking space provided is very small and narrow, there are customer complaints that the indoor space is not cold. The aim of this research is to analyze the influence of ambient conditions on repurchase intention. The type of research used in this research is descriptive with quantitative data. The types of data used in this research are primary and secondary data. The population of this research is visitors who come to Northeast Coffee. The research sample consisted of 203 consumers with a sampling technique using non-probability sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this research show that ambient conditions are in the quite good category, namely 63.05%. And the repurchase intention variable is in the good category, namely 36.95%. The influence of ambient conditions (X) on repurchase intention (Y) with a score of 8.3% and 91.7% is influenced by other factors. Furthermore, the results of simple linear regression analysis obtained a calculated F value of 18.191 with sig. 0.000 < 0.05.